Development of Micro Power Generator Using LPG-Fueled Microtubular Solid Oxide Fuel Cells. (2nd June 2015) - Sumi, Hirofumi; Yamaguchi, Toshiaki; Suzuki, Toshio; Shimada, Hiroyuki; Hamamoto, Koichi; Fujishiro, Yoshinobu
Abstract : Solid oxide fuel cells (SOFCs) can, in principle, directly use hydrocarbon fuels such as methane and liquefied petroleum gas (LPG). It was previously found that nickel-gadolinia doped ceria (Ni-GDC) anode has high durability under LPG utilization in SOFCs. However, the performance under direct LPG utilization was low compared to hydrogen fuel, because anode polarization resistance increased by internal reforming. Carbon was slightly deposited on the Ni-GDC anode after direct LPG utilization for 100 h at 650 o C. In this work, a catalytic partial oxidation reformer was developed for LPG utilization, and high performance was obtained using reformate gas as well as hydrogen without carbon deposition on the Ni-GDC anode for 100 h at 650 o C. Furthermore, microtubular SOFC stacks were developed using mass production technologies, and a proto-type 200 W micro power generator was demonstrated via NEDO project entitled "Technology Development for Promoting SOFC Commercialization".